When is poem truly equivalent to LHM? A comparison of complication rates during the learning curve - wong, wei jin; Nik Muhamad Affendi, Nik Arsyad; siow, sze li; mahendran, han alexander; Lau, Peng Choong; Ho, Shiaw Hooi; Mahadeva, Sanjiv (2022)
INTRODUCTION: Per-Oral Endoscopic Myotomy (POEM) has been shown to be an effective treatment for Achalasia, but the endoscopic technique required is complex and not routinely performed. We believe that, for any new procedure, competency can be demonstrated when the complication rate of a new procedure (POEM) equals that of an established one, ie Laparoscopic Heller’s Myotomy + Fundoplication (LHM+F). METHODS: A multicentre, retrospective cohort, comparing complication rates during the learning curve of POEM to a historical cohort of LHM+F, was conducted. A direct head-to-head comparison was performed, followed by a population pyramid of complication frequency. Case sequence was then divided into blocks of 5, and the complication rates during each block was compared to the historical cohort. RESULTS: A total of 123 cases ( LHM+F n=60, POEM n=63) were analysed. Mean age was lower for the POEM group (41.7 years vs 48.1 years, p = 0.03), but there was no difference in gender nor type of Achalasia. The POEM group recorded a shorter overall procedural time (125.9 minutes vs 144.1 minutes, p = 0.023) and longer myotomies (10.1cm vs 6.2cm, p = 0.023). Complication rates were higher in the POEM group (20.6% vs 10.0%, p=0.10), but was not statistical significant. Complication frequency tapered off dramatically after the 25th case in the sequence, and subsequently equalled that of LHM+F. Length of stay was shorter for the POEM group (3.4 days vs 4.8 days, p = 0.014). The post-procedural findings favoured LHM+F, with the post-procedural Eckardt scores significantly lower (0.4 vs 1.6, p < 0.001) and the usage of PPIs lower in this group (20.7% vs 39.4%, p = 0.03). CONCLUSION: POEM is challenging even for experienced endoscopists. From our data, complication rates between POEM and LHM+F equalize after approximately 25 POEMs.